Basic Periodontal Treatment Improves Periodontal Inflamed Surface Area Without Adverse Events in Patients Receiving Direct Oral Anticoagulants: A Retrospective Clinical Study with an Animal Model - Ryousuke Fujimori; Yuri Taniguchi; Kazuhisa Ouhara; Shunsuke Miyauchi; Shinji Matsuda; Naoya Kuwahara; Shoya Ueda; Yitong Hou; Masaru Shimizu; Misako Tari; Shoko Kono; Tomoyuki Iwata; et al. (Biomedicines, 2026)
Background/Objectives: The optimal management of periodontal treatment in patients receiving direct oral anticoagulants (DOACs) remains poorly established, and bleeding concerns may lead clinicians to delay or limit treatment. We evaluated the clinical efficacy and safety of nonsurgical periodontal treatment in patients receiving DOAC therapy. Methods: This retrospective study included 67 patients receiving continuous DOAC therapy (edoxaban, apixaban, dabigatran, or rivaroxaban) who underwent nonsurgical periodontal treatment without drug discontinuation. Pocket probing depth, bleeding on probing, the periodontal inflamed surface area (PISA), the periodontal epithelial surface area (PESA), and serum inflammatory cytokine levels were evaluated. A ligature-induced-periodontitis mouse model was also used to assess the effect of apixaban on alveolar bone loss. Results: Nonsurgical periodontal treatment significantly reduced the PISA (42.9%) and PESA (10.8%) in the overall DOAC cohort, with no postoperative bleeding complications. Significant reductions in periodontal parameters were seen in the edoxaban (PISA: 44.2%, PESA: 10.9% reduction), apixaban (PISA: 45.6%, PESA: 11.7% reduction), and dabigatran (PISA: 61.3%, PESA: 16.1% reduction) groups, with no significant changes in the rivaroxaban group. Baseline PISA was positively correlated with baseline serum levels of interleukin-4 (r = 0.33), interleukin-1 beta (r = 0.29), interleukin-6 (r = 0.25), and interleukin-10 (r = 0.30). In the mouse model, apixaban administration did not aggravate ligature-induced alveolar bone loss. Conclusions: Basic periodontal treatment appears to be safe and effective for patients prescribed DOACs and may reduce local periodontal inflammation, resulting in systemic inflammatory burden. These findings support proactive periodontal intervention in patients receiving DOAC therapy, regardless of the specific anticoagulant used.